2011
DOI: 10.22358/jafs/66221/2011
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different compounds in some essential oils on <i>in vitro</i> gas production

Abstract: The aim of this study was to determine the effect of essential oils (EO) of oregano, ORE (Origanum vulgare); black seed, BSD (Nigella sativa); laurel, LAU (Laurus nobilis); cumin, CUM (Cumminum cyminum); garlic, GAR (Allium sativum); anise, ANI (Pimpinella anisum), and cinnamon, CIN (Cinnamomum verum) on in vitro gas production (IVGP) and IVGP kinetics of barley, wheat straw and soyabean meal. IVGP values were determined by using rumen liquor from three dry Holstein cows. The findings of this study indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
4
11
0
1
Order By: Relevance
“…The improvement noticed in nutrients digestibility with feeding CUP, in the present study, may be due to that cumin stimulates the secretion of pancreatic enzymes, compounds necessary for proper digestion and nutrient assimilation, and may also have anti-carcinogenic properties which improve animal status as reported by Nurdin and Arief (2009), and also improve cellulose digestion (Kilic et al, 2011) as well as increase CF digestibility. In addition, the observed increase in nutrients digestibility with feeding GAP or CUP could be ascribed as a result of the antimicrobial properties of garlic and cumin which could lead to suppressed rumen digestion (Ikyume et al 2017).…”
Section: Nutrients Digestibility and Nutritive Valuessupporting
confidence: 75%
“…The improvement noticed in nutrients digestibility with feeding CUP, in the present study, may be due to that cumin stimulates the secretion of pancreatic enzymes, compounds necessary for proper digestion and nutrient assimilation, and may also have anti-carcinogenic properties which improve animal status as reported by Nurdin and Arief (2009), and also improve cellulose digestion (Kilic et al, 2011) as well as increase CF digestibility. In addition, the observed increase in nutrients digestibility with feeding GAP or CUP could be ascribed as a result of the antimicrobial properties of garlic and cumin which could lead to suppressed rumen digestion (Ikyume et al 2017).…”
Section: Nutrients Digestibility and Nutritive Valuessupporting
confidence: 75%
“…Surprisingly, Tekippe et al (2013) stated that in cows supplemented with a blend of EOC based on eugenol and cinnamaldehyde total tract NDFD increased by 1.8% to 9.0%. Certainly, these contradicting results reflect differences between the tested EOC, used doses (often not economically suitable for commercial livestock), as well as diet/substrate characteristics (Kilic et al, 2011), but may also reflect analytical differences either of the in situ method or the selected NDF analysis. The wide variation in methodologies analysing NDFD is well documented and in several studies differences between the in situ and the in vitro methods were reported (e.g., Spanghero et al, 2003;Bender et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, based on the available data, it is conceivable that NDFD and dry matter (DM) digestibility (DMD) can be affected differently and their combined interpretation can further explain the activity of these bioactive additives. Data on the effects of different doses added to diets of different energy concentration and composition have been reviewed by Hart et al (2008) and recently by Cobellis et al (2016); also some substrate effects were reported by Kilic et al (2011) who examined gas production of barley, soyabean meal and wheat straw treated with different doses of oregano, black seed, laurel, cumin, garlic, anise and cinnamon EO. The effects of specific compounds were reported by various authors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that during ruminal fermentation, 2-12% of dietary energy intake is lost as methane, which contributes considerably to global warming (Jonhson and Johnson, 1995 (Kilic et al, 2011;Akcil and Denek, 2013;Thao et al, 2014;Kumar et al, 2012;Kouazounde et al, 2015). Several researchers have tested the leaves of Laurus nobilis and Eucalyptus globulus trees and their secondary metabolites for their anti-methanogenic potential.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have tested the leaves of Laurus nobilis and Eucalyptus globulus trees and their secondary metabolites for their anti-methanogenic potential. It has been reported that L. nobilis and E. globulus trees and their secondary metabolites have potential to mitigate enteric methane emissions (Kilic et al, 2011;Akcil and Denek, 2013;Kouazounde et al, 2014;Thao et al, 2014Thao et al, , 2015. L. orientalis, which can grow to 10-15 m, is a native tree species in Turkey whose leaves contain essential oils similar to those in the leaves of L. nobilis and E. globules.…”
Section: Introductionmentioning
confidence: 99%